FACTORS OF DEVELOPMENT OF AUTOPEDAGOGICAL COMPETENCE OF THE FUTURE TEACHER AND ADVANCED SCIENTIFIC IDEAS - Malika Mominovna Parpieva (Bright Mind Publishing, 2025)
This article discusses the factors for developing the autopedagogical competence of a future teacher and the design of a plan for conducting research work in stages in accordance with the proposed scientific ideas, as a result of the formation and development of autopedagogical competence of the future teacher, it is stated that it is possible to determine and study the impact of the main psycho-physiological and social determinants on all structural and functional components of the development of autopedagogical competence and the mechanisms of interaction between them.
Keywords: Autopedagogy, autopedagogical competence, psycho-physiological, functional components, mechanism, pedagogical system, factor.